Sodium hyaluronate eye drops treatment for superficial corneal abrasion caused by mechanical damage: a randomized clinical trial in the People’s Republic of China - Lin T; Gong L (Dove Medical Press, 2015)
Tong Lin, Lan Gong Department of Ophthalmology, Eye and ENT Hospital of Fudan University, Shanghai, People’s Republic of China Purpose: To evaluate the effectiveness and safety of 0.3% sodium hyaluronate (HA) compared to recombinant bovine basic fibroblast growth factor (rb-bFGF) for the treatment of corneal epithelial abrasion caused by mechanical damage in Chinese patients.Methods: Thirty patients were randomly assigned to the HA or rb-bFGF treatment group. The HA group was treated with 0.3% HA and 0.5% levofloxacin, and the rb-bFGF group was treated with topical rb-bFGF and 0.5% levofloxacin. The primary endpoint was the clinical effectiveness rates at day 3. Secondary endpoints were the dimensions of the wound area and the percentage of wound closure.Results: After 3 days of treatment, the clinical effectiveness rates of the HA group and the rb-bFGF group were 86.67% (13/15) and 93.33% (14/15), respectively. The dimensions of the wound area were reduced from 9.83±8.50 to 0.02±0.06 mm2 for the HA group at day 7, and from 10.58±9.94 to 0.02±0.07 mm2 for the rb-bFGF group. At day 3, the wound closure was almost complete in both groups; 94.73% in the HA group compared to 95.77% in the rb-bFGF group (P>0.05).Conclusion: Topical 0.3% HA provided a promising treatment for superficial corneal abrasion caused by mechanical damage in a manner similar to rb-bFGF. Keywords: sodium hyaluronate, superficial corneal abrasion, bovine basic fibroblast growth factor